Characterization of bacterial cellulose films combined with chitosan and polyvinyl alcohol: Evaluation of mechanical and barrier properties. (15th July 2019) - Cazón, Patricia; Velázquez, Gonzalo; Vázquez, Manuel
Highlights: Bacterial cellulose is a raw material to develop biodegradable composites. The developed films may be used for applications in medicine, cosmetics, and food industry. Poly(vinyl alcohol) and chitosan improve bacterial cellulose films properties. Developed films showed optical barrier properties against UV-radiation. Transparent films with adequate visual appearance were obtained. Abstract: Bacterial cellulose (BC) produced by Komagataeibacter xylinus is a biomaterial with a unique three-dimensional structure. To improve the mechanical properties and reinforce the BC films, they were immersed in polyvinyl alcohol (0–4%) and chitosan (0–1%) baths. Moisture content, mechanical properties and water vapour permeability were measured to assess the effect of polyvinyl alcohol and chitosan. The morphology, optical, structural and thermal properties were evaluated by scanning electron microscopy, spectral analysis, thermogravimetry and differential scanning calorimetry. Results showed that moisture content was significantly affected by the chitosan presence. Tensile strength values in the 20.76–41.65 MPa range were similar to those of synthetic polymer films. Percentage of elongation ranged from 2.28 to 21.82% and Young's modulus ranged from 1043.88 to 2247.82 MPa. The water vapour permeability (1.47 × 10 −11 –3.40 × 10 −11 g/m s Pa) decreased with the addition of polyvinyl alcohol. The developed films own UV light barrier properties and optimal visual appearance.